Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T14:01:03+01:00
A) -7+3y+9+2y=2+5y
b) x-3x+2y=-2x+2y
c) -5x+4y-y-7x-9=-12x+3y-9
d) 4x+5-x-4+x-3x=x+1
e) -14k+9k-13+k+3+4k=-10
f) -3k+2m+5m-7+k-m=-2k+6m-7
g) 2x-4+3x-2=5x-6
h) x-3y-2x+6y=-x+3y
2010-03-17T14:02:20+01:00
A) 2 + 5y
b) -2x +2y
C) -12x - 6y
d)x + 5
e) k - 10
f) 2k +6m - 7
g)5x - 6
h) -x +3 y
2010-03-17T14:02:49+01:00
A) -7+3y+9+2y = 2+5y
b) x-3x+2y= -2x+2y
c) -5x+4y-y-7x-9y= -12x-6y
d) 4x+5-x-4+x-3x= x+1
e) -14k+9k-13+k+3+4k= -10
f) -3k+2m+5m-7+k-m= -2k+6m-7
g) 2x-4+3x-2=5x-6
h) x-3y-2x+6y=-3x+3y